The Effect of Performative and Social Legitimation on Brand Equity: A Customer – Based Approach - Zarkada, Anna K.; Kapareliotis, Ilias (My University, 2012)
Customer brand support is intensively used among marketers and marketing academics. It designs the support that the consumer markets give to the brand building thus or enhancing brand equity variables. This support refers mainly to the brand equity variables as they have been introduced by Aaker (1992). Consumer based brand equity is not only a financial indicator for contemporary companies balance sheets; it a leading factor for companies’ social and performative legitimation, leading the company to a unique brand orientation, which makes it more competitive. This brand orientation is examined in this research paper as an outcome of both legitimation types previously mentioned, and customer based brand equity stemming from customers based support. The paper empirically explores these relationships based on researcher administered questionnaire survey of 244 British and Greek easy jet customers.
Keywords: Customer support for the brand; Customer based brand equity; Social performative legitimation; Brand oriented company